Long-term Visual and Ocular Sequelae in Patients With Congenital Cytomegalovirus Infection - Jin, Haoxing Douglas; Demmler-Harrison, Gail J; Coats, David K; Paysse, Evelyn A; Bhatt, Amit; Edmond, Jane C; Yen, Kimberly G; Steinkuller, Paul; Miller, Jerry (The Pediatric infectious disease journal, 2017)
Cytomegalovirus (CMV) is the most common congenital viral infection in the United States. Visual and ocular sequelae in adolescents and adults who are congenitally infected with CMV have not been well studied. Better understanding of the long-term visual and ocular sequelae can help with early detection, intervention and appropriate educational accommodations. This study evaluated 237 patients (77 symptomatic, 109 asymptomatic and 51 control) who underwent a series of age-appropriate ophthalmologic, audiologic and neurodevelopmental examinations from 1982 to 2013. The frequency and etiology of visual impairment and other nonophthalmologic findings were recorded for each patient. Ophthalmologic findings were tabulated, and risk factors for abnormalities were analyzed. Fourteen of the 77 (18.2%) symptomatic and none of the asymptomatic and control subjects had severe visual impairments (P ≤ 0.006). Moderate visual impairment did not differ between symptomatic and asymptomatic subjects. Three asymptomatic subjects had retinal scars. The most common visual or ocular sequelae in the symptomatic group were strabismus (23.4%), chorioretinal scars (19.5%), cortical visual impairment (14.3%), nystagmus (14.3%) and optic nerve atrophy (11.7%). Three symptomatic patients had delayed visual deterioration because of later occurring retinal disorders: peripheral retinal scar, rhegmatogenous retinal detachment and Coats' disease. Symptomatic CMV patients experienced more ophthalmologic sequelae and significantly worse visual outcomes than asymptomatic CMV and control patients. Later occurring retinal disorders were found in symptomatic patients, and there is no clear evidence that CMV can reactivate in the retinas of children who were congenitally infected. Major risk factors for severe visual impairment included symptomatic status, optic nerve atrophy, chorioretinitis, cortical visual impairment and sensorineural hearing loss.